MODERN BUILDING MATERIALS BASED ON MINERAL AND CHEMICAL ADDITIVES USED IN THE CONSTRUCTION PROCESS AND THEIR USE IN EUROPEAN COUNTRIES (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the properties, technological advantages of modern building materials based on mineral and chemical additives, as well as the experience of their use in European countries. Advanced solutions for increasing energy efficiency, environmental safety, durability and quality indicators in the construction process are considered. The possibilities of adapting these experiences to the conditions of Uzbekistan are also analyzed.